Perbedaan Pengaruh Latihan Agility Hurdle Drill dan Agility Ladder Drill terhadap Kemampuan Dribbling dalam Permainan Sepakbola pada Atlet SSB Asri Gemolong Tahun 2026 - Ahmad Khoirul Anam; Pipit Fitria Yulianto; Bagus Kuncoro (MAN Insan Cendekia Jambi, 2026)
This study aims to compare the effectiveness of Agility Hurdle Drill and Agility Ladder Drill training on the dribbling skills of SSB Asri Gemolong athletes in 2026. The data analysis revealed a significant difference in the impact of the two training methods, as evidenced by a calculated t-value greater than the t-table value (3.995 > 2.145) at a 5% significance level. Between the two interventions, the Agility Ladder Drill method (Group 2) proved to be superior and more effective than the Agility Hurdle Drill (Group 1) in improving ball dribbling skills, achieving a higher percentage of improvement (8.007% > 8.000%).